MARKETING COMMUNICATIONS AND ACCOUNTING INTEGRATION: A HOLISTIC STRATEGY FOR BUSINESS SUCCESS - Loso Judijanto; Silvia Ekasari; Hadenan Towpek (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
In an increasingly complex business world, the integration between marketing communications and accounting is key to a company's success. This holistic approach allows companies to more eflectively manage resources and make strategic decisions. By combining the power of marketing communications and the rigour of accounting, companies can create more targeted strategies. This helps in measuring the eflectiveness of marketing campaigns, allocating budgets more wisely, and understanding the financial impact of each marketing activity. This integration also encourages transparency and cooperation between departments, creating a more unified organisational culture. The result is faster and more accurate decision- making, and a better ability to respond to market changes. By implementing this strategy, companies can improve their competitiveness, operational efficiency, and ultimately, profitability. This integrated approach is becoming increasingly important in the digital age, where data and analytics play a key role in business success.